Improving Employee Motivation: Analysis of the Influence of Performance Appraisal System, Workload, and Compensation - Alasyhari, Haris Fuad; Lestari, Setyani Dwi (Newinera Publisher, 2025)
This research analyze the influence of the performance assessment system, workload, and compensation on employee motivation at KPP Pratama Jakarta XYZ. A quantitative approach with descriptive and explanatory design was was utilized to numerically assess the relationships among these variables and provide an overview of the current conditions in the research environment. Data were collected through questionnaires and analyzed using statistical methods with the assistance of SPSS software. The results show that, partially, the performance assessment system has a positive but not significant influence on employee motivation. Workload has a significant negative influence, indicating that excessive work pressure can reduce motivation. On the other hand, compensation has a significant positive influence, demonstrating that financial and non-financial incentives play a vital role in enhancing motivation. Simultaneously, the three variables have a significant influence on employee motivation, contributing 26% to the variability of motivation. These findings underscore the importance of improving the performance assessment system and managing workload to enhance organizational effectiveness. Furthermore, providing optimal compensation is a critical strategy for motivating employees to achieve their best performance. This research offers insights for KPP Pratama Jakarta XYZ's management in designing more relevant and impactful policies to boost employee motivation and productivity.